Two “Official” Languages of Work: Explaining the Persistence of Inequitable Access to French as a Language of Work in the Canadian Federal Public Service - Gaspard, Helaina (Université d'Ottawa / University of Ottawa, 2014)
Canada’s official languages policy makes English and French the country’s official languages in federal institutions. The policy has succeeded in fostering equitable representation of both official languages groups in the federal public service and has improved capacities for the public service to serve the citizenry in its official language of choice. It is a puzzle however, that despite these advances, the Canadian federal public service continues to operate predominantly in English when both official languages on paper are equal languages of work. To explore this puzzle this dissertation asks: why, despite the promise of the Official Languages Act (OLA) 1969 for choice in language of work and the OLA 1988 that made the choice a claimable right, is there inequitable access to French as a language of work in the federal public service? Framed through a historical institutionalist approach and layering, this project analyzes the implementation of the official languages program in the federal public service from 1967-2013. This thesis argues that the implementation of the official languages program could not challenge the federal public service’s path dependency to operate predominantly in English. By analyzing the roles of actors and institutions that influenced the process, this dissertation finds that lack of structural change, inadequate managerial engagement and a false sense that official languages are engrained in the public service, can explain the persistence of English as the dominant language of work.
Keywords: Official Languages; Institutionalism; Canadian federal public service; Bilingualism; Language of work; Language rights; Language policy; Policy implementation; Institutional change